Kepemimpinan pendidikan yang transformasional: Konsep kepemimpinan transformasional, ciri-ciri kepala sekolah transformasional, contoh-contoh pemimpin transformasional di sekolah - Alifah, Ilfina; Sidiq, Muhammad Umar (Maliki Interdisciplinary Journal, 2024)
Transformational leadership is a leadership approach that aims to inspire and motivate people to reach their fullest potential and achieve significant change in the organization. In transformational leadership, a leader influences subordinates in a positive way and builds strong relationships based on trust, respect, and self-development. This research is classified as qualitative research by collecting references from various sources both from journals and books. The results of this study explain that transformational leaders influence subordinates in a positive way and build strong relationships based on trust, appreciation, and self-development. By motivating employees to reach their full potential, transformational leadership can create an organizational culture that is oriented towards achievement, innovation, and growth.